Ibnu Rusyd dan Rasionalisasi Wahyu: Telaah Kritis terhadap Relasi Akal dan Agama dalam Filsafat Islam - Muhammad Mursyid Mumtaz; Susan Apriyanti; Najla Zalfa Izdihar; Nadzira Hasna; Muhamad Parhan (CV. ITTC INDONESIA, 2025)
This study explores Ibn Rushd’s philosophical thought in rationalizing the relationship between reason and revelation within Islamic philosophy. The background of this research stems from historical tensions between philosophical reasoning and religious orthodoxy, especially as seen in the debate between Ibn Rushd and Al-Ghazali. This article applies a qualitative method using literature review techniques from relevant primary and secondary sources. The findings reveal that Ibn Rushd promotes a harmonious approach by dividing human intellectual comprehension into three levels: rhetorical, dialectical, and demonstrative. Through the demonstrative (burhani) and allegorical interpretation (ta’wil), he argues that there is no inherent contradiction between revelation and rationality if both are properly understood. This study highlights the contemporary relevance of Ibn Rushd’s perspective in advancing Islamic education that is inclusive, critical, and rational. His thoughts contribute not only to Islamic epistemology but also offer a philosophical foundation for engaging in meaningful dialogue between religion, philosophy, and science in the modern world.